2014
DOI: 10.1371/journal.pone.0100499
|View full text |Cite
|
Sign up to set email alerts
|

An Important Role of α-Hemolysin in Extracellular Vesicles on the Development of Atopic Dermatitis Induced by Staphylococcus aureus

Abstract: Skin barrier disruption and dermal inflammation are key phenotypes of atopic dermatitis (AD). Staphylococcus aureus secretes extracellular vesicles (EVs), which are involved in AD pathogenesis. Here, we evaluated the role of EVs-associated α-hemolysin derived from S. aureus in AD pathogenesis. α-hemolysin production from S. aureus was detected using western blot analyses. The cytotoxic activity of α-hemolysin on HaCaT keratinocytes was evaluated by measuring cell viability after treating cells with soluble and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 34 publications
(49 reference statements)
4
83
0
1
Order By: Relevance
“…Our data shows that the 13565, 14458, and 25923 strains carry several hemolysin genes and enterotoxin A (13565) or enterotoxin B (14458) genes. Strain 14458, a known enterotoxin B and hemolysin A–producing reference strain, and strain 25923, a biofilm‐forming reference strain, showed no effects significantly different to controls. The 13565 strain that severely compromised the TJ structure in our study is known to produce enterotoxin A and hemolysin B .…”
Section: Discussionmentioning
confidence: 94%
“…Our data shows that the 13565, 14458, and 25923 strains carry several hemolysin genes and enterotoxin A (13565) or enterotoxin B (14458) genes. Strain 14458, a known enterotoxin B and hemolysin A–producing reference strain, and strain 25923, a biofilm‐forming reference strain, showed no effects significantly different to controls. The 13565 strain that severely compromised the TJ structure in our study is known to produce enterotoxin A and hemolysin B .…”
Section: Discussionmentioning
confidence: 94%
“…It has been proposed that Th2 cytokines can also increase α-toxin-induced keratinocyte toxicity [62]. Murine models with subcutaneous injections of α-toxin display increased inflammation at the site of injection [63]. Although high concentrations of α-toxin are toxic to host cells, low concentration can also stimulate keratinocyte cytokine production leading to increased inflammation as well [64].…”
Section: S Aureus Virulence Factors In Ad Severitymentioning
confidence: 99%
“…S. epidermidis has also been shown in both murine and keratinocyte models to have a protective role through the amplification of endogenous AMPs [80,81]. Finally, there is evidence that S. epidermidis can prevent S. aureus biofilm formation in the nasal cavities as well as produce its own AMPs to prevent SAgs (SEA/B, TSST-1) Non-specific APC-mediated T cell activation, keratinocyte cytokine production [56][57][58][59] α-Toxin Keratinocyte lysis and TNF-α production [60][61][62][63][64] δ-Toxin Mast cell degranulation and inflammation [65] V8 and ETA/B DSG-1 cleavage leading to both increased desquamation and skin inflammation [66][67][68] Protein A Keratinocyte TNF-α production [64] PSM Keratinocyte inflammation [69] SAg superantigen, SEA and SEB enterotoxins A and B, TSST-1 toxin shock syndrome toxin 1, ETA and ETB exfoliative toxins A and B, PSM phenol-soluble modulins other pathogens from colonizing the skin [37,82]. Therefore, increased S. epidermidis colonization in AD skin may represent a way for the skin to naturally prevent increased S. aureus colonization in AD.…”
Section: Effect Of Other Bacterial Strains On Ad Pathogenesismentioning
confidence: 99%
“…Most importantly, EVs can be purified from body fluids, including plasma and urine, thereby providing an excellent tool to probe the effect of bacterial infection on a systemic level 16. We also previously reported that S. aureus -derived EVs induced AD-like inflammation in the skin and were causally related to the pathogenesis of AD 1718…”
Section: Introductionmentioning
confidence: 99%